Case Report: Early detection of lung carcinoid in an asymptomatic individual by blood-test initiated PET-CT imaging - Burg, Simon; Smeets, Ralf; Gosau, Martin; Failing, Katja; Grust, Audrey Laure Céline (Frontiers in Oncology, 2023)
We present the case of a 53-year-old woman who was diagnosed with early-stage lung cancer by targeted cancer screening consisting of an immunological biopsy-based blood test followed by radiological imaging. The PanTum Detect blood test detects the biomarkers Apo10/DNaseX and Transketolase-like 1 (TKTL1) in circulating macrophage-like cells from peripheral blood samples to identify asymptomatic individuals with a high risk for malignancy. The elevated blood test values initiated an 18F-FDG PET/CT visualization for further clarification. In this case, imaging indicated a lung carcinoma in the right upper lobe. A biopsy confirmed the presence of a lung carcinoma, which was removed surgically. Histologic examination revealed a typical I A2 carcinoid, which was completely removed, making further therapy obsolete.